Does organizational growth contribute to profitability? Evidence from Malaysian public listed companies - Ting I.W.-K.; Kweh Q.-L.; Chan Y.-C. (Universiti Malaysia Sarawak, 2023)
This paper aims to examine the impact of organizational growth on the profitability of Malaysian public listed companies for the period of 2001-2010. The sample consists of a balanced panel data of 240 companies from various sectors listed on the Main Board of Bursa Malaysia. The study develops multiple regression models to test the impact of organizational growth on firm performance. The results reveal that organizational growth has an impact on profitability. Two independent variables, viz. total assets growth and fixed assets growth, are found to be significantly affecting the performance of our sample firms. These findings may reveal that Malaysian public listed firms should particularly focus on total assets growth and fixed assets growth to maximize their returns. © 2014, Universiti Malaysia Sarawak, All Rights Reserved. .